PENERAPAN PRAKTIK KEPERAWATAN BERBASIS BUKTI PURSED LIP BREATHING PADA PASIEN DENGAN PENYAKIT PARU OBSTRUKTIF KRONIK DI RUANG RSU PUSAT PERSAHABATAN JAKARTA - Sitorus, Seven (Fakultas Ilmu Kesehatan, 2015)
Background: Chronic Obstruction Pulmonary Disease (COPD) is disease characterized by obstruction air flow in the breath not wholly reversible. One treatment can be done on improving exercise tolerance is exercise respiration as pursed lip breathing ( PLB ). Purse lip breathing is a techniques of breathing carried out to expelling air by creating power through in move closer /pursed lips. Purpose: provide an illustration of the application of the practice of evidence based nursing of pursed lip breathing in patients COPD in RSUP Persahabatan Jakarta. Method: the implementation of the practice of evidence based nursing pursed lip breathing is applied to 12 people sample ( 10 men and 2 women ) diagnosed with COPD exacerbation. Result: the majority of sex respondents is man as many as 10 ( 83,3 % ) persons and women as many as 2 ( 16,7 % ) a person .mean the age of respondents is 61,5 years ± 10.4 .mean the value of PEF ( Peak Expiratory Flow ), the value of the saturation oxygen , the value of respiratori rate before the intervention in a consecutive manner is 131.6 ± 44.6; 92.1 ± 2.44; 31.5 ± 2 . While value after the intervention is 175.0 ± 60.0; 97,1 ± 1.6; 22,6 ± 1.7 with P value = 0.001, α = 0.05. Conclusions: there are significant influence the application of pursed lip breathing between before and after the intervention in patients COPD. Advice: Intervention evidence based nursing can be applied to all patients COPD so reached the quality of care of nursing based on research